Genetic control of CCL24, POR, and IL23R contributes to the pathogenesis of sarcoidosis - Meguro, Akira; Ishihara, Mami; Petrek, Martin; Yamamoto, Ken; Takeuchi, Masaki; Mrazek, Frantisek; Kolek, Vitezslav; Benicka, Alzbeta; Yamane, Takahiro; Shibuya, Etsuko; Yoshino, Atsushi; Isomoto, Akiko; et al. (Communications biology, 2020)
Sarcoidosis is a genetically complex systemic inflammatory disease that affects multiple organs. We present a GWAS of a Japanese cohort (700 sarcoidosis cases and 886 controls) with replication in independent samples from Japan (931 cases and 1,042 controls) and the Czech Republic (265 cases and 264 controls). We identified three loci outside the HLA complex, CCL24, STYXL1-SRRM3, and C1orf141-IL23R, which showed genome-wide significant associations (P < 5.0 × 10-8) with sarcoidosis; CCL24 and STYXL1-SRRM3 were novel. The disease-risk alleles in CCL24 and IL23R were associated with reduced CCL24 and IL23R expression, respectively. The disease-risk allele in STYXL1-SRRM3 was associated with elevated POR expression. These results suggest that genetic control of CCL24, POR, and IL23R expression contribute to the pathogenesis of sarcoidosis. We speculate that the CCL24 risk allele might be involved in a polarized Th1 response in sarcoidosis, and that POR and IL23R risk alleles may lead to diminished host defense against sarcoidosis pathogens.
Keywords: Genetic Predisposition to Disease; alely; lokus kvantitativního znaku; systém (enzymů) cytochromů P-450; celogenomová asociační studie; genotyp; jednonukleotidový polymorfismus; Alleles; receptory interleukinů; Sarcoidosis; Genotype; mužské pohlaví; Cytochrome P-450 Enzyme System; Receptors, Interleukin; Quantitative Trait Loci; Japonsko; Polymorphism, Single Nucleotide; ženské pohlaví; genetické asociační studie; chemokin CCL24; Humans; sarkoidóza; odds ratio; Japan; Genetic Association Studies; genetická predispozice k nemoci; Female; Chemokine CCL24; Genome-Wide Association Study; lidé; Male; Odds Ratio